2006
DOI: 10.1111/j.1365-246x.2006.02967.x
|View full text |Cite
|
Sign up to set email alerts
|

Crust and upper mantle structure of a continental backarc: central North Island, New Zealand

Abstract: S U M M A R YNear vertical and wide-angle seismic data provide evidence for a gradational crust-mantle boundary in a depth range of 15-20 km beneath the Central Volcanic Region (CVR), New Zealand. This volcanic area includes the Taupo Volcanic Zone and is a direct extension of Tonga-Kermadec oceanic backarc spreading into continental lithosphere. Long-range seismic refraction data show velocities of 6 km s −1 and less within the top 15 km of the crust of the CVR. At a depth of 15 km compressional seismic veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
118
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(135 citation statements)
references
References 75 publications
15
118
2
Order By: Relevance
“…Te Punga (1957) indicated that a radial drainage pattern may have existed at some point on the Mt Stewart-Halcombe Anticline, while Jackson et al (1998) drew attention to what may be the remnants of a radial drainage pattern at the southern end of the Pohangina Anticline. Pillans (1983) noted that the southern Wanganui Basin may currently be undergoing minor tectonic subsidence, rather than uplift, and Stratford and Stern (2006) have recently drawn attention to the nature of vertical plate kinematics to the north -a pattern of crustal extension in a continental back-arc zone. Hence, the exact nature of active tilting and any drainage development that predates current tilting makes any analysis of long-term tectonic effects difficult to deconvolve.…”
Section: Discussionmentioning
confidence: 98%
“…Te Punga (1957) indicated that a radial drainage pattern may have existed at some point on the Mt Stewart-Halcombe Anticline, while Jackson et al (1998) drew attention to what may be the remnants of a radial drainage pattern at the southern end of the Pohangina Anticline. Pillans (1983) noted that the southern Wanganui Basin may currently be undergoing minor tectonic subsidence, rather than uplift, and Stratford and Stern (2006) have recently drawn attention to the nature of vertical plate kinematics to the north -a pattern of crustal extension in a continental back-arc zone. Hence, the exact nature of active tilting and any drainage development that predates current tilting makes any analysis of long-term tectonic effects difficult to deconvolve.…”
Section: Discussionmentioning
confidence: 98%
“…tion in the resistivity (Heise et al, 2007). A further significant drop of resistivity can be seen at about 15 km depth, which coincides with the base of the quartzo-feldspathic crust (Harrison and White, 2006;Stratford and Stern, 2006) beneath which underplating is believed to be occurring, and a higher proportion of melt is present (Charlier et al, 2005).…”
Section: Deep Structure and Heat Sourcesmentioning
confidence: 92%
“…Southward, the Taupo volcanic zone passes into the South Wanganui Basin, where, in the northern sector, marine sedimentary sequences are currently up-doming and normal and reverse faulting and synclinal and anticlinal folding are taking place (Kamp et al, 2004;Pulford and Stern, 2004;Villamor and Berryman, 2006b). Ruapehu is thus in a unique position where volcanic landscapes abut nonvolcanic terrains, and subduction tectonics give way to strike-slip faulting to the south (Wood and Davy, 1994;Stratford and Stern, 2006).…”
Section: Introductionmentioning
confidence: 96%